REALISME MAGIS DALAM NOVEL BELOVED KARYA TONI MORRISON - , Niko Fediyanto; , Prof. Dr. Faruk, S.U. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The main problem analyzed in this research is to study magical realism as a global phenomenon emerging in United States of America inside a contemporary work of literature, i.e. Beloved. The writer presented a magical world as an opposition of realism. The writer positioned myth in opposition to modernity, and periferal as opposed to central in social, ideology, and discursive the relation of black and white. In order to answer the problems, magical realism is applied as a perspective. This research used magical realism theory to see the mythical symptom of peripheral area as magical world in the influence of modernity. The first step did with this theory to by seeing the degree of magical realism in the novel, that is by determining the five elements of magical realism, then seeing the relation of the five elements and finding the function of the structure , then determining the degree of magical realism. After the elements are identified, the next is determining the social, idealism, and discursive context to see the connection between Beloved and the context. The writer acknowledge the existence of magical world in the real world but locate the magic in uncertain, exist but not seen. The writer stated that the magic to the real world. The merge of the magic and the real categorize this novel as magical realism one.